Correction: Preparation and evaluation of nanocellulose–gold nanoparticle nanocomposites for SERS applications. Issue 6 (26th February 2016) - Wei, Haoran; Rodriguez, Katia; Renneckar, Scott; Leng, Weinan; Vikesland, Peter J.
Abstract : Correction for 'Preparation and evaluation of nanocellulose–gold nanoparticle nanocomposites for SERS applications' by Haoran Wei, et al., Analyst, 2015, 140, 5640–5649.